Cost-effective bioethanol production at low content of nitrogen source from carob syrup - Raposo, Sara (2014)
Ethanol, as biofuel, has received great interest in the latest decades due to its potential as an alternative transport fuel. Nowadays, ethanol can be produced through fermentative processes, using sugar rich agricultural raw material and it may have a significant role in reducing environmental impact of fossil fuels.